Glacioisostasy and lake-level change at Moosehead lake, Maine - Balco, G.; Belknap, D. F.; Kelley, J. T. (Quaternary Research, 1998)
Reconstructions of glacioisostatic rebound based on relative sea level in Maine and adjacent Canada do not agree well with existing geophysical models. In order to understand these discrepancies better, we investigated the lake-level history of 40-km-long Moosehead Lake in northwestern Maine. Glacioisostasy has affected the level of Moosehead Lake since deglaciation ca. 12,500 C-14 yr B.P. Lowstand features at the southeastern end and an abandoned outlet at the northwestern end of the lake indicate that the lake basin was tilted down to the northwest, toward the retreating ice sheet, by 0.7 m/km at 10,000 C-14 yr B.P. Water level then rose rapidly in the southeastern end of the lake, and the northwestern outlet was abandoned, indicating rapid relaxation of landscape tilt. Lowstand features at the northwestern end of the lake suggest that the lake basin was tilted to the southeast at ca. 8750 C-14 yr B.P., possibly as the result of a migrating isostatic forebulge. After 8000 C-14 yr B.P., water level at the southeastern end was again below present lake level and rose gradually thereafter. We found no evidence suggesting that postglacial climate change significantly affected lake level. The rebound history inferred from lake-level data is consistent with previous interpretations of nearby relative sealevel data, which indicate a significantly steeper and faster-moving ice-proximal depression and ice-distal forebulge than geophysical models predict. (C) 1998 University of Washington.
Zm315Times Cited:9Cited References Count:46